IMPLEMENTASI PENGEMBANGAN KEMAMPUAN KEMANDIRIAN ANAK TUNAGRAHITA SEDANG USIA DINI : Studi Kasus tentang Kemandirian Anak Tunagrahita Sedang di SD-LB Sekolah Luar Biasa (SLB) C Purnama Asih, Bandung - Destri Ayu Prihatin, - (2017)
The objective of the research is because it is still a lack of stimulation of self-reliance for children with Intellectual disability (now the preferred term for mental retardation). One aspect that the author wants to see is the independence or self-reliance of the child with mental retardation. This study aims to determine the development of independence of children with mental retardation. The research method used in this research is qualitative with case study approach. Participants in this study were seven childrens with medium mental retardation age 8 years, one teacher, and two parents. The data in this study were collected through observation, interview and documentation study related to the independence of the child. The results show that there are some children who have not been independent, such as marching, wearing and taking off their shoes, eating, drinking, brushing, and washing hair. In addition to children who are not independent. There are two forms of communication between parents and teachers regarding the independence of children with mental retardation, which is using a direct communication and communication through social media (WhatsApp). The teacher is making lesson implementation plan and for the implementation itself, teacher more using direct practice to develop the self-reliance on children with mental retardation. For the media itself, teacher use the images and videos as a media to support learning. Teacher also accompany the children in their learning process and it's provided in the classroom and outside the classroom as well. Teacher also experience obstacles in establishing a child with mental retardation, as an example, the child ignores the teacher's direction. According to the teacher the child with mental retardation is very inert lazy. In addition to constraints faced, teacher also have a solution which is by teaching habituation to children. The recommendation of this research is teacher should keep their eyes on which children are already independent and not independent and parents should also train children to be independent as well.---- Penelitian ini dilatar belakangi karena masih kurangnya stimulasi kemandirian untuk anak tungrahita sedang. Salah satu aspek yang ingin dilihat penulis yaitu kemandirian anak tunagrahita. Penelitian ini bertujuan untuk mengetahui pengembangan kemandirian anak tunagrahita. Metode penelitian yang digunakan dalam penelitian ini ada kualitatif dengan pendekatan studi kasus. Partisipan dalam penelitian ini adalah tujuh anak tunagrahita sedang usia delapan tahun, satu guru, dan dua orang tua. Data dalam penelitian ini dikumpulkan melalui observasi, wawancara dan studi dokumentasi terkait kemandirian anak tunagrahita. Hasil penelitian menunjukkan bahwa ada beberapa anak yang belum mandiri seperti berbaris, memakai dan melepas sepatu, makan, minum, menyikat gigi, dan mencuci rambut. Terdapat dua bentuk komunikasi antara orang tua dan guru terkait kemandirian anak tunagrahita, yaitu komunikasi langsung dan komunikasi melalui sosial media (whatsapp). Implementasi pengembangan kemandirian pada anak tunagrahita yaitu guru membuat RPP, dan dalam pelaksanaannya guru lebih banyak praktek langsung. Untuk medianya sendiri guru menggunakan media gambar dan video untuk menunjang pembelajaran. Pendampingan guru dalam proses pembelajaran diberikan di dalam kelas dan di luar kelas. Guru juga mengalami kendala dalam memandirikan anak tunagrahita seperti anak yang menghiraukan ajakan guru, dan menurut guru anak tunagrahita sangat malas. Selain kendala yang dihadapi guru juga mempunyai solusi yaitu dengan mengajarkan pembiasaan kepada anak. Rekomendasi dari penelitian ini adalah guru sebaiknya mengawasi mana anak yang sudah mandiri dan belum mandiri. Serta orang tua juga sebaiknya melatih anak untuk mandiri.